Application of Asset Management System Using Barcode (Case Study PT. Indonesia Toray Synthetics) - Ria Wulandari; Yuni Roza; Naufal Fadhil Alwarits (CCIT (Creative Communication and Innovative Technology) Journal, 2021)
Asset Management at PT. Indonesia Toray Synthetics is still done manually, it also burdens admin in inputting and searching for asset data. The utilization of information technology in managing the asset management system will greatly assist PT. Indonesia Toray Synthetics by scanning items using barcodes, displaying the history of incoming and outgoing goods, and being able to manage asset management reports based on certain periods in real time. In making this system and research, the writer uses the SWOT (Strengths, Weaknesses, Opportunities & Threats) method, and UML (Unified Modeling language) for system design oriented which has been implemented in the PHP (Hypertext) programming language and Sublime Text applications. With the application of this asset management system, it will be able to facilitate the data collection and data search of assets as well as to control the stock rotation of goods in the company.